Aussies, Rogues and Slackers: Simon Hanselmann’s Megg, Mogg and Owl Comics as Contemporary Instances of Rogue Literature - Scott, Ronnie (Text Matters: A Journal of Literature, Theory and Culture, 2019)
This paper examines the Megg, Mogg and Owl stories of Simon Hanselmann, an Australian artist whose serialized comics both depict acts of contemporary roguery committed by a group of friends in an inner city sharehouse and test the generic limits of its own storytelling conventions, thereby becoming contemporary instances of “rogue texts.” The paper positions the adventures of Megg, a witch, Mogg, her familiar, Owl, their housemate, and associated characters including Booger and Werewolf Jones as contemporary variations of both the Australian genre of grunge fiction and the broad international tradition of rogue literature. It shows how Megg, Mogg, Owl and their friends use the structure of the sharehouse to make their own rules, undertake illegal behaviour, and respond to the strictures of mainstream society, which alongside legal restrictions include normative restrictions on gender and behaviour. It shows the sharehouse as a response to their economic, as well as cultural and social conditions. The paper then shows how Megg and particularly Owl come up against the limitations of the permissiveness and apparent security of their “rogue” society, and respond by beginning to “go rogue” from the group. Meanwhile, the text itself, rather than advancing through time, goes over the same chronology and reinscribes it from new angles, becoming revisionist and re-creative, perhaps behaving roguishly against the affordances of episodic, vignette form. The paper argues that Simon Hanselmann’s Megg, Mogg and Owl comics can be understood as contemporary rogue texts, showing characters responding to social and generic limits and expressing them through a restless and innovative comics text.